Enhancing quality of life in individuals with cerebral palsy: a systematic review and meta-analysis of physiotherapy interventions - Passos, Adrielle Andrade; Santos, Franciely Oliveira de Andrade; Arida, Ricardo Mario; Brogin, João Angelo Ferres [UNESP]; Faber, Jean; López-Ortiz, Citlali; Teixeira-Machado, Lavínia (Taylor & Francis, 2025)
Purpose: This systematic review examined studies that addressed physiotherapy intervention approaches to the Quality of Life (QoL) of people with Cerebral Palsy (CP). Materials and methods: We conducted a comprehensive search strategy in five databases (PEDro, PubMed, Web of Science, Scopus, and Google Scholar) until 12 February 2024. We assessed the included studies’ methodological quality and statistical description using the PEDro scale. We performed a meta-analysis using random-effect models to synthesize the results of different physiotherapy interventions and their impact on QoL. Results: We included 37 studies that met the eligibility criteria, involving people with CP aged between 18 months and 53 years across all levels of the Gross Motor Function Classification System (n = 1541). The included studies present a considerable variation in scales, duration, types of therapies, and number of sessions. The meta-analysis demonstrated significant standardized mean differences in favor of alternative physiotherapy compared to conventional physiotherapy, considering a single general index of QoL. Conclusion: Findings from the included studies indicate that alternative physiotherapy can improve the QoL for people with CP, but the results vary. A personalized, comprehensive approach is essential, emphasizing high-frequency, guided activities. More rigorous research is needed for those with GMFCS levels IV and V.
Keywords: Cerebral palsy; meta-analysis; physiotherapy; quality of life; systematic review